ПРОБЛЕМА ІНШОГО В СУЧАСНОМУ СОЦІАЛЬНО-ГУМАНІТАРНОМУ ПІЗНАННІ (ЧАСТИНА ПЕРША) - ВАДИМ, ПАЛАГУТА (Humanities Studies, 2023)
The article was devoted to the analysis of the structuralist and poststructuralist model of the Other (Others) as the basis for the formation of social subjectivity and its identity. Based on the comparative method, a comparison of these models was carried out. The principles of construction, similarities and differences between these models of the Other were identified. Thus, the model of the Other traditional philosophical structuralism with its absolutization of the "process without a subject" imposes from the outside, at times, an unacceptable, alien identity to the subject. A typical example of the use of this model of the Other is M. Foucault's dispositifs of power or L. Althusser's interpellation, involved in the construction of ideological identity. Particular attention in the study was paid to the hybrid model of the Other, which indicates a rather complex process of subjectivation taking place at an uncontrolled, unconscious level, an example of which was shown to us by the subject of the unconscious of J. Lacan. It is shown that the model of the Other poststructuralism differs significantly from the structuralist one, which allows us to consider subjectivity differently. This model of the Other(s) further allows us to expand and modify the application of the poststructuralist approach, which emphasizes the virtual social fields and places (everywhere and nowhere) of the ugly Other. The contours of further study of the problem of transformation and incorporation of the model of the "Other" into modern social structures are outlined, which significantly modifies the role of collective identity for the subject. But what transformations with models of the Other are taking place now in modern society, when the subject seems to have believed in the prospects of "free" construction of his identity without direct correlation with the Other, becomes a prospect for future research.